Kajian Etnomatematika Berbasis Budaya Lokal Tradisional Ditinjau Dari Perspektif Pendidikan Multikultural - Marni Serepinah; Nina Nurhasanah (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
Indonesia is rich in culture. The diverse traditional local cultures provide materials to be explored and linked to mathematics learning. The ethnomathematics is a scientific approach that connects mathematics and culture. This study aims to provide an overview and rationalization of the importance of the role of ethnomathematics in multicultural education. As a result, it can be studied because culture is introduced not only through the social sciences but also through the exact sciences via mathematics. The research method in this study is qualitative, using the systematic mapping study method or systematic analysis study to describe the research mapping on ethnomathematics that has been studied. The following are the findings of the research: (1) Various traditional local cultural media, such as traditional houses, woven products, batik, and others, are the media that are widely studied using ethnographic and descriptive qualitative research. The research subjects were cultural experts or descendants of royal lineages. Very little research provides examples of the use of materials in the classroom and according to their measurement capacity. (2) The ethnomathematics plays a role in a multicultural education by exploring various cultures so that students can get to know the multiculturalism of Indonesian nation. The meaningfulness of the mathematics learning and culture is used to make the learning effective in multicultural classrooms.